Continuous positive airway pressure therapy might be an effective strategy on reduction of atrial fibrillation recurrence after ablation in patients with obstructive sleep apnea: insights from the pooled studies - Li, Feng; He, Chang-Jian; Ding, Chun-Hua; Wang, Ru-Xing; Li, Hui (Frontiers in Neurology, 2023)
Background: Obstructive sleep apnea (OSA) is an independent and modifiable risk factor in the initiation and maintenance of atrial fibrillation (AF). However, the effective of the continuous positive airway pressure (CPAP) on AF patients with OSA after ablation is elusive.Methods: Cochrane Library, PubMed, Embase, and Web of Science were systematically searched up to 1 February 2023. Studies comprising the AF recurrence rate between the CPAP therapy group and non-CPAP therapy group for the AF patients with OSA were included. Meanwhile, trial sequential analysis (TSA) was conducted to adjust the lower statistical power and random error in this study.Subgroup analysis identified the potential determinants for the AF recurrence rate with CPAP therapy.Results: A total of eight studies including 1,231 AF patients with OSA were eligible.Compared with non-CPAP treatment group, CPAP treatment group was statistically associated with a lower AF recurrence rate (risk ratio [RR], 0.58; P=0.000). TSA indicated the firm evidence favoring CPAP group for AF recurrence risk. Three significant intervention-covariate interactions for AF recurrence was identified, including study design, non-paroxysmal AF (PAF) proportion, and CPAP treatment strategy.Our study suggests that CPAP therapy might be an effective strategy on reducing AF recurrence post-ablation for AF patients with OSA. The CPAP treatment strategy and the non-PAF proportion might be the possible determinants on AF 4 recurrence for AF patients with OSA after ablation.